Analysis of hedge fund replication products - Candreia, Robin Joël (2016)
Hedge fund replication has generated significant academic interest and received increased attention from a broad base of investors. This is mainly driven by its competitive after-fee returns along with its superior liquidity, transparency and lower due diligence costs. The purpose of this dissertation is therefore to provide a detailed critical analysis of available hedge fund replication products. The results show that the performance of replication products can vary widely, and replication approaches are still a work in progress. However, they offer an attractive way to enhance the returns of a portfolio while simultaneously diversifying risk because they show a low correlation to traditional asset classes.